The Constituent Assembly and its Functions in the Constitutional Democratic System - Cairo Roldán, Omar (2006)
This paper highlights the need to examine the role of a constituent assembly within a democratic and constitutional system. To this end, a detailed analysis of the issue is undertaken on the basis of doctrine and constitutional history. It is concluded that the purpose of a constituent assembly is to establish a constituent power and to reform the constitution. Constituent power is the ability of a society to create or reform fundamental rights and the structure of government. Thus, the Constituent Assembly is the way in which the people exercise this power with the aim of amending the existing constitution or creating a new one. However, the author points out that there is one element that cannot be excluded by this power, and that is constitutional democracy. In this sense, this article provides a detailed study that helps to understand what a Constituent Assembly implies as a key entity for the strengthening and development of democracy, highlighting its importance for the stability and legitimacy of a country's legal system.